Physical and Chemical Properties and Methods of Control of Pantoprazol Sodium Sesquihydrate (Review) - V. A. Shelekhova; K. R. Savelyeva; S. V. Polyakov; V. N. Shestakov (Разработка и регистрация лекарственных средств)
Introduction. Pantoprazole sodium sesquihydrate is a proton pump inhibitor. This substance is used in the treatment of peptic ulcer of the duodenum or stomach in the acute phase, including those associated with the use of non-steroidal anti-inflammatory drugs.Text. Pantoprazole is sodium 5-(difluoromethoxy)-2-[(RS)-[(3,4-dimethoxypyridin-2-yl)methyl]sulfinyl]benzimidazol-1-ide sesquihydrate in its structure. The substance is readily soluble in water and ethyl alcohol. The identification of pantoprazole is confirmed by infrared absorption spectrophotometry, as well as by a positive reaction to sodium ion. For the assay of this substance chemical and physico-chemical methods are used. The first group of methods includes titration in a non-aqueous medium with perchloric acid and permanganatometry. Physico-chemical methods used for pantoprazole assay are spectrophotometry and HPLC. The most commonly used method is direct spectrophotometry associated with the measurement of optical density at a wavelength of the maximum absorption of pantoprazole in various solvents. In addition, spectrophotometric methods of assay are known, based on the study of the absorption of colored pantoprazode reaction products. The derivative spectrophotometry is used for the analysis of its preparations. The control of the content of impurities and pantoprazole in the substance and its dosage forms is carried out, as a rule, using HPLC.Conclusion. An analysis of the literature has shown that this substance is unstable. Therefore, this feature of pantoprazole must be considered when choosing excipients when developing a dosage form. The preferred method for analyzing pantoprazole preparations is HPLC, since it is possible to determine the substance in the presence of other compounds, which will allow one to control the quantitative content and stability of pantoprazole in the preparation.